Bisnis dan Dakwah Dalam Tradisi Media (Kopi) di Provinsi Aceh - Mukhsinuddin, Mukhsinuddin; Hamsa, Amrizal; Bargie, Gamal (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
The rapid growth of coffee shops in Aceh has established the region as a coffee production area. Among these establishments, some have embraced an Islamic concept in their business model by integrating religious content into their offerings, exemplified by the program